Implementasi prinsip non-diskriminasi dalam perlindungan hak asasi manusia di Indonesia: Tantangan dan prospek reformasi hukum - Aulia, Andini Rizka (Maliki Interdisciplinary Journal, 2026)
The implementation of the principle of non-discrimination in the protection of human rights in Indonesia is a crucial component in achieving social justice and equal rights for all citizens. This study aims to analyze the implementation of the principle of non-discrimination in the protection of human rights in Indonesia, the various challenges faced, and the prospects for legal reform in strengthening human rights protection. The method used in this study is a qualitative research method with a literature review approach through various journals, scientific articles, and academic sources related to human rights. The research findings indicate that Indonesia has a sufficiently strong legal foundation for human rights protection; however, its implementation still faces various social, cultural, political, and legal obstacles. Discrimination against minority and vulnerable groups still frequently occurs due to low public awareness, weak law enforcement, and suboptimal state protection of human rights. Legal reform is necessary through the strengthening of regulations, the enhancement of law enforcement professionalism, the strengthening of human rights institutions, as well as public education and awareness regarding the importance of tolerance and respect for human rights. With effective legal reform, the implementation of the principle of non-discrimination in Indonesia is expected to function more effectively and be able to foster a society that is just, tolerant, and socially equitable.